Quantile connectedness analysis and portfolio strategies among crude oil, gold, exchange rate, the US stock market, traditional and sustainable indices: Evidence from Thailand - Surachai Chancharat; Nongnit Chancharat (Sustainable Futures, 2025)
Using the quantile connectedness method developed by Ando, Greenwood-Nimmo [1], this study investigates the dynamic connectedness relationships that exist between crude oil, gold, exchange rate, the US stock market, traditional (Stock Exchange of Thailand: SET) and sustainable (Thailand Sustainability Investment: THSI) indices of Thailand. According to the data, return spillovers are more prominent under negative market conditions compared to optimistic ones. The traditional and sustainable indexes are net contributors to return spillovers, regardless of the quantiles used. Moreover, a substantial spillover is observed during periods of extreme stress, such as the situation with COVID-19 and the war between Russia and Ukraine. Another point to consider is that spillovers are more noticeable in lower quantiles as opposed to higher quantiles. The lowest, middle, and upper quantiles of the connectedness index show negative effects from crude oil, gold, and currency rates.